2010
DOI: 10.1111/j.1462-5822.2010.01469.x
|View full text |Cite
|
Sign up to set email alerts
|

The bacterial effectors EspG and EspG2 induce a destructive calpain activity that is kept in check by the co-delivered Tir effector

Abstract: Bacterial pathogens deliver multiple effector proteins into eukaryotic cells to subvert host cellular processes and an emerging theme is the cooperation between different effectors. Here, we reveal that a fine balance exists between effectors that are delivered by enteropathogenic E. coli (EPEC) which, if perturbed can have marked consequences on the outcome of the infection. We show that absence of the EPEC effector Tir confers onto the bacterium a potent ability to destroy polarized intestinal epithelia thro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 55 publications
2
23
1
Order By: Relevance
“…Recent evidence suggests that the interaction of Intimin with the Tir effector (13) is a prerequisite event that is necessary for the TJ-disrupting activities of the other effectors, providing EPEC with additional control over effector function (13). This shows that EspF requires additional EPEC-mediated signaling to disrupt the TJs, and this is further supported by a separate study in which expression of EspF alone within epithelial cells had no observable effect on tight junctions (1).…”
Section: Espf-mediated Cellular Changes Linked Directly To Diarrheasupporting
confidence: 65%
See 2 more Smart Citations
“…Recent evidence suggests that the interaction of Intimin with the Tir effector (13) is a prerequisite event that is necessary for the TJ-disrupting activities of the other effectors, providing EPEC with additional control over effector function (13). This shows that EspF requires additional EPEC-mediated signaling to disrupt the TJs, and this is further supported by a separate study in which expression of EspF alone within epithelial cells had no observable effect on tight junctions (1).…”
Section: Espf-mediated Cellular Changes Linked Directly To Diarrheasupporting
confidence: 65%
“…This function was the first ascribed to EspF (35) and was also used to identify EspF's molecular chaperone CesF (16). The authors of the former study speculated that EspF may not be acting alone in the disruption of TJs (35), and indeed, subsequent studies have shown that EspF cooperates with the EPEC effectors Map, Tir, EspG, and NleA to mediate rapid TJ disruption (11,13,53,54). The molecular details of EspF-mediated TJ disruption are slowly becoming unraveled, and while mitochondrial targeting is not involved (58), the recruitment of tight junctional proteins to bacterium-induced pedestals by EspF has been implicated (45).…”
Section: Espf-mediated Cellular Changes Linked Directly To Diarrheamentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that both EPEC and EHEC can induce rearrangements of the actin cytoskeleton [41]. The EPEC EspF protein collaborated with the effectors Map, Tir, EspG and NleA to interfere with TJs [42][43][44]. Moreover, EspF can cause actin sequestration and recruit junctional proteins, such as occludin, claudin, ZO-1 and ZO-2, to the pedestals, inducing the redistribution and loss of transepithelial electrical resistance, disruption of paracellular permeability and depolymerization of actin.…”
Section: Resultsmentioning
confidence: 99%
“…tEPEC OMPs in fully differentiated Caco-2 cells monolayers induce changes in adherens junctions, leading to the dissociation of the cadherin/␤-catenin complex and the cytoplasmic redistribution of ␤-catenins through the activation of PKC-␣ signaling (689). In fully differentiated Caco-2 cells, EspG and EspG2, through their activation of the host cysteine protease calpain, lead to a loss of TER and a rapid cell loss and necrosis, a phenomenon that is increased in the absence of Tir (690). The EspG effector and its homologue Orf3 are both involved in microtubule disruption in fully differentiated Caco-2 cells, but EspG alone has no effect on TER, whereas EspG combined with Orf3 decreases TER (691).…”
Section: Structural and Functional Injuries At The Junctional Domainmentioning
confidence: 99%